2006
DOI: 10.1016/j.yexcr.2006.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Translesion synthesis in mammalian cells

Abstract: DNA damage blocks the progression of the replication fork. In order to circumvent the damaged bases, cells employ specialised low stringency DNA polymerases, which are able to carry out translesion synthesis (TLS) past different types of damage. The five polymerases used in TLS in human cells have different substrate specificities, enabling them to deal with many different types of damaged bases. PCNA plays a central role in recruiting the TLS polymerases and effecting the polymerase switch from replicative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 36 publications
0
73
0
Order By: Relevance
“…Several lines of evidence have shown that PCNA monoubiquitination occurs both in yeast and higher eukaryotes, primarily in response to the DNA damage-induced stalling at DNA replication forks (13,(27)(28)(29). In the present study we have demonstrated that in addition to the monoubiquitination of PCNA, the chromatinbound PCNA polyubiquitination is enhanced by DNA damage that stalls DNA replication forks, but not by ␥-irradiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that PCNA monoubiquitination occurs both in yeast and higher eukaryotes, primarily in response to the DNA damage-induced stalling at DNA replication forks (13,(27)(28)(29). In the present study we have demonstrated that in addition to the monoubiquitination of PCNA, the chromatinbound PCNA polyubiquitination is enhanced by DNA damage that stalls DNA replication forks, but not by ␥-irradiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA has recently been shown to be monoubiquitylated in response to UV light, which enhances its interaction with and activation of pol (57). PCNA was previously shown to interact with p300/CBP (cAMP-responsive element-binding protein-binding protein) histone acetyltransferase and may be acetylated (51,58).…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is also listed as a BER DNA synthesis and ligation related protein and is modified in many ways, including phosphorylation, acetylation, SUMO and ubiquitin, as listed in Table III. There are many detailed reviews that characterize the varied post-translational modifications of PCNA and the impact of these modifications on PCNA-protein interactions [132][133][134].…”
Section: Ber Dna Synthesis and Ligation Proteinsmentioning
confidence: 99%